METAL NANOPARTICLES AFFECT GLOBAL DNA METHYLATION LEVEL AND GENE EXPRESSION IN EARLY GERMINATION OF SOYBEAN - T. M. Linh1; P. T. Hoe; N. C. Mai; N. H. Chau; N. T. Van (Journal of Animal and Plant Sciences, 2021)
Nowadays, metal-based nanoparticles have been widely applied at a small dose for plant-growth and agronomic yield promotion, leading to significant economic and environmental benefits. The interaction mechanism between nanoparticles (NPs) and plants has been reported, however, not been completely elucidated yet. Therefore, this study aims to look at the global DNA methylation status and the expression of germination- related genes of NP treated soybean plants. The analysis indicated that the global DNA methylation, one important epigenetic mechanism in controlling gene expression, of NP treated plants was obviously changed from the control plants, especially in primary roots. The DNA methylation levels in primary roots were decreased significantly at 18 hours and increased at 48 hours after seed treatment with Fe or Co NPs and these values were opposite with Cu, ZnO NP treatment. Together with changes in DNA methylation, the expression of representative germination-related genes such as Glyma.08G018000, Glyma.07G007000, Glyma.09G21700, Glyma.04G096500 and Glyma.02G163900, which encoding for enzymes involved in ethylene biosynthesis and mobilization of seed reserves was increased under all NP treatments. The obtained results suggest that metal-based nanoparticles stimulate seed germination and seedling growth of soybean via regulation of DNA methylation and related gene expression.
Keywords: DNA methylation; gene expression; germination; metal nanoparticles; seed treatment; soybean